Efektivitas Model Project Based Learning (PjBL) Berbantuan Media Riri Cerita Anak Interaktif terhadap Pemahaman Unsur Intrinsik Cerita - Sarah Aulia Ibrahim; Arifin Ahmad; Yuni Indriani (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2026)
This study was motivated by the low Indonesian language learning outcomes of fifth-grade students at SDN Jatisari. The study aimed to determine the effectiveness of the Project-Based Learning (PjBL) model, supported by the "Riri Interactive Children's Stories" media, on students' understanding of the intrinsic elements of stories. A quantitative approach was employed using a quasi-experimental method with a non-equivalent control group design. The implementation of the PjBL model supported by the "Riri Interactive Children's Stories" media demonstrated an improvement in students' understanding of intrinsic story elements; this was evidenced by research results showing a significant difference between the experimental and control classes. The average pretest score for the experimental class was 55.71, rising to 82.89 in the posttest, whereas the control class scores went from 54.24 to 58.53. The t-test significance value was < 0.001, and the effect size was 4.480 (categorized as a large effect). Thus, it is concluded that the Project-Based Learning (PjBL) model supported by the "Riri Interactive Children's Stories" media is effective in enhancing the understanding of intrinsic story elements among fifth-grade students at SDN Jatisari.